2001
DOI: 10.1021/jm000275p
|View full text |Cite
|
Sign up to set email alerts
|

A Potent, Nonpeptidyl 1H-Quinolone Antagonist for the Gonadotropin-Releasing Hormone Receptor

Abstract: Extensive development of the structure-activity relationships of a screening lead determined three important pharmacophores for gonadotropin-releasing hormone (GnRH) receptor antagonist activity. Incorporation of the 3,4,5-trimethylphenyl group at the 3-position, 2-(2(S)-azetidinyl)ethoxy group at the 4-position, and N-4-pyrimidinylcarboxamide at the 6-position of the quinolone core resulted in the identification of 4-(2-(azetidin-2(S)-yl)ethoxy)-7-chloro-2-oxo-3-(3,4,5-trimethylphenyl)-1,2-dihydroquinoline-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The following chemical structures (collectively referenced as "pharmacoperones") were utilized; those of the quinolone class are prefaced by the letter "Q" and those of the indole class by the letters "IN" and were produced by Merck and Company (Ashton et al, 2001a;Ashton et al, 2001b;Ashton et al, 2001c;DeVita et al, 1999a;DeVita et al, 1999b;DeVita et al, 2001;Walsh et al, 2000): Q89, (7-chloro-2-oxo-4-{2-[(2S)-piperidin-2-yl]ethoxy}-N-pyrimidin-4-yl-3-(3,4,5-trimethylphenyl)-1,2-dihydroquinoline-6-carboxamide); Q76, (N-(7-chloro-3-(3,5- -chloro-6-[(6,7-dimethoxy-3,4-…”
Section: Methodsmentioning
confidence: 99%
“…The following chemical structures (collectively referenced as "pharmacoperones") were utilized; those of the quinolone class are prefaced by the letter "Q" and those of the indole class by the letters "IN" and were produced by Merck and Company (Ashton et al, 2001a;Ashton et al, 2001b;Ashton et al, 2001c;DeVita et al, 1999a;DeVita et al, 1999b;DeVita et al, 2001;Walsh et al, 2000): Q89, (7-chloro-2-oxo-4-{2-[(2S)-piperidin-2-yl]ethoxy}-N-pyrimidin-4-yl-3-(3,4,5-trimethylphenyl)-1,2-dihydroquinoline-6-carboxamide); Q76, (N-(7-chloro-3-(3,5- -chloro-6-[(6,7-dimethoxy-3,4-…”
Section: Methodsmentioning
confidence: 99%
“…However, at the rat GnRH receptor a 10-fold lower affinity was found. 26 Compound 8 was also characterized in in vivo studies. Intravenous administration of 3 mg/kg of 8 resulted in 79% suppression of LH and 92% suppression of testosterone blood levels in primates.…”
Section: B Quinolin-2-one Derivativesmentioning
confidence: 99%
“…GnRH agonists and antagonists developed to date are injectable or depot formulations of GnRH peptide analogs (Bouchard, 1996). Although other laboratories have reported active nonpeptide GnRH antagonists (Walsh et al, 2000;Ashton et al, 2001a,b;DeVita et al, 2001;Zhu et al, 2002a,b), few have shown oral activity in animal models (Cho et al, 1998;Besecke et al, 2001;Ashton et al, 2001c). An unmet clinical need still exists for an orally available GnRH receptor antagonist.…”
mentioning
confidence: 99%